Galerkin Finite Element Study on the Effects of Variable Thermal Conductivity and Variable Mass Diffusion Conductance on Heat and Mass Transfer*Supported the Higher Education Commission (HEC) of Pakistan for the financial support under NRPU vides No. 5855/Federal/NRPU/R&D/HEC/2016. (July 2018) - Qureshi, Imran Haider; Nawaz, M.; Rana, Shafia; Zubair, T.
Abstract: This article investigates the effects of variable thermal conductivity and variable mass diffusion coefficient on the transport of heat and mass in the flow of Casson fluid. Numerical simulations for two-dimensional flow induced by stretching surface are performed by using Galerkin finite element method (GFEM) with linear shape functions. After assembly process, nonlinear algebraic equations are linearized through Picard method and resulting linear system is solved iteratively using Gauss Seidal method with simulation tolerance 10 − 8 . Maximum value of independent variable η is searched through numerical experiments. Grid independent study was carried out and error analysis is performed. Simulated results are validated by comparing with already published results. Parametric study is carried out to explore the physics of the flow. The concentration increases when mass diffusion coefficient is increased. The concentration and thermal boundary layer thicknesses increase when ϵ 1 and ϵ are increased. The effect of generative chemical reaction on concentration is opposite to the effect of destructive chemical reaction on the concentration.